(Not) Surviving the Night: A Nocturnal Ethnography of the Hospital Corridor - Davies, Fiona (Ethnologies, 2022)
While traditionally regarded as one of the many liminal nocturnal spaces within the often-labyrinthine complexes of contemporary hospitals, the corridor is not inscribed with specific activities, rules of conduct or dress codes. Instead, particularly at night they become in-between places of ambiguity and ambivalence. As a family member of an ICU patient, frequently you are asked to step outside while medical staff undertake some procedure. This can occur at any time of the night. In the early hours after midnight the family can be left to wander the darkened corridors, led on by the glow of the vending machines all safely locked inside the building and yet out of ICU. This experience of liminal nocturnal temporality by going beyond that expected of being in transition, can linger to become semi-permanent, and therefore alter the perception of the transition from life to death so that it may feel suspended, stalled, or never-ending.